miR-299-3p suppresses cell progression and induces apoptosis by downregulating PAX3 in gastric cancer - Wang Zhenfen (De Gruyter, 2021)
Gastric cancer (GC) is ranked the fourth leading cause of cancer-related death, with an over 75% mortality rate worldwide. In recent years, miR-299-3p has been identified as a biomarker in multiple cancers, such as acute promyelocytic leukemia, thyroid cancer, and lung cancer. However, the regulatory mechanism of miR-299-3p in GC cell progression is still largely unclear. Cell viability and apoptosis tests were performed by CCK8 and flow cytometry assay, respectively. Transwell assay was recruited to examine cell invasion ability. The interaction between miR-299-3p and PAX3 was determined by the luciferase reporter system. PAX3 protein level was evaluated by western blot assay. The expression of miR-299-3p was downregulated in GC tissues and cell lines (MKN-45, AGS, and MGC-803) compared with the normal tissues and cells. Besides, overexpression of miR-299-3p significantly suppressed proliferation and invasion and promoted apoptosis in GC. Next, we clarified that PAX3 expression was regulated by miR-299-3p using a luciferase reporter system, qRT-PCR, and western blot assay. Additionally, downregulation of PAX3 repressed GC cell progression. The rescue experiments indicated that restoration of PAX3 inversed miR-299-3p-mediated inhibition on cell proliferation and invasion. miR-299-3p suppresses cell proliferation and invasion as well as induces apoptosis by regulating PAX3 expression in GC, representing desirable biomarkers for GC diagnosis and therapy.